Does Public Scientific Research Complement Industry R&D Investment? The Case of NIH Supported Basic and Clinical Research and Pharmaceutical Industry R&D - Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This research investigates the hypothesis that publicly funded scientific research complements private R&D investment in the pharmaceutical industry. New microlevel data on public research investment by the U.S. National Institutes of Health allow measures of basic and clinical research in seven medical areas to be included in a distributed lag model explaining pharmaceutical R&D investment. Using a panel of therapeutic classes observed over eighteen years, the analysis finds strong evidence that public basic and clinical research are complementary to pharmaceutical R&D and, thereby, stimulate private industry investment. However, differences in the relevance and degree of scientific and market uncertainty between basic and clinical public research lead to differences in the magnitude and timing of the pharmaceutical investment response. The results indicate that a dollar increase in public basic research stimulates an additional 8.38 in pharmaceutical investment after eight years. The industry R&D response to public clinical research is smaller in magnitude and shorter in duration with a dollar increase in public clinical research stimulating an additional 2.35 in pharmaceutical investment over a three year period.
Keywords: O32; H51; L65; C23; 330; R&D; pharmaceuticals; NIH; distributed lag models; Pharmazeutische Forschung; Öffentliche Forschung; Industrielle Forschung; Investition; Schätzung; USA